2019
DOI: 10.1016/j.foodchem.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus application rate on Mentha spicata L. grown in deep flow technique (DFT)

Abstract: The present study evaluated the impact of phosphorus application rate on plant growth and physiological parameters, antioxidant activity, chemical composition, and essential oil yield and composition of hydroponically grown spearmint plants. Increased P levels resulted in high dry matter content of the aerial part. Antioxidant activity of spearmint leaves was significantly higher at the highest P levels. Although essential oil yield was not affected, essential oil composition varied among the studied P levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This result was consistent with the study of Lu et al who reported that the PA of green and red perilla was not affected by EC or light intensity [33]. The effect of EC and certain minerals in the nutrition solution on the synthesis of essential oils from various plant species have been shown [55][56][57]. Although there was no significant difference in PA concentration in the present study, it showed a trend of increasing this value as the content of N, S, and P in the nutrient solution increased with increasing EC levels.…”
Section: Biochemical Parameterssupporting
confidence: 92%
“…This result was consistent with the study of Lu et al who reported that the PA of green and red perilla was not affected by EC or light intensity [33]. The effect of EC and certain minerals in the nutrition solution on the synthesis of essential oils from various plant species have been shown [55][56][57]. Although there was no significant difference in PA concentration in the present study, it showed a trend of increasing this value as the content of N, S, and P in the nutrient solution increased with increasing EC levels.…”
Section: Biochemical Parameterssupporting
confidence: 92%
“…This phenolic acid was the major compound found in this endangered species, which corresponded to 71.4% and 78.7% of the total phenolic compounds quantified in aerial and root parts, respectively. Lower levels of rosmarinic acid than those found in the E. viviparum root have been reported in other Lamiaceae, such as rosemary (Rosmarinus officinalis L.; 6.9 ± 0.2 mg g −1 extract; Gonçalves et al (2019), and 68.5 mg g −1 extract; Ribeiro et al (2016)) and spearmint (Mentha spicata L. 73.4 ± 0.8 mg g −1 extract; Chrysargyris et al (2019)).…”
Section: Phenolic Compositionmentioning
confidence: 72%
“…[ [100][101][102][103][104][105] Anticarcinogenic properties a. Piperitenone oxide is the first potential medical benefits of anticarcinogenic properties.…”
Section: Mint (Menthaspicata L)mentioning
confidence: 99%